Vitapan 3D-master shade guide showed no fluorescence emission - Yong-Keun Lee; Bin Yu; Ho-Nam Lim (Wolters Kluwer Medknow Publications, 2012)
Objectives: To determine the fluorescence property of Vitapan 3D-Master shade guide tabs with a spectrophotometer. Materials and Methods: Fluorescence property of 29 shade tabs, in both of original and ground-to-flat forms, was determined by a reflection spectrophotometer. Color difference (ΔEFNx01ab-FL) by the inclusion and exclusion of the UV component of a standard daylight simulator (CIE standard illuminant D65) was calculated to determine the fluorescence color change. Fluorescence peak was expressed as the difference in spectral reflectance values by the UV component. Results and Conclusion: ΔE FNx01ab-FL values were in the range of 0.2 to 2.7 (mean: 1.2±0.6) for the original and 0.5 to 1.6 (mean: 0.9±0.1) for the ground-to-flat tabs, which was significantly different based on paired t-test (p<0.05); however, fluorescence peak was not detected in all the shade tabs. Therefore, fluorescence property of Vitapan 3D-Master shade guide should be modified to have similarfluorescence property of natural teeth and corresponding restorative materials.